2017
DOI: 10.1155/2017/5719461
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Vitamin D in Association with Age, Inflammatory Cytokines, Anthropometric Parameters, and Lifestyle Factors in Older Adults

Abstract: Vitamin D deficiency is present even in sunny regions. Ageing decreases pre-vitamin D production in the skin and is associated with altered cytokine profile. We performed a multivariate analysis considering lifestyle factors, anthropometric, and inflammatory markers according to seasonal variation in Mexican healthy older adults. The same cohort was followed during 12 months. Vitamin D deficiency/insufficiency was found in 91.3% of the subjects despite living in appropriate latitude (25°40′0″N). 25(OH)D levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 63 publications
2
33
3
3
Order By: Relevance
“…Positive correlations have also been found between vitamin D and TNF-alpha levels (r = 0.347; p = 0.009), which is contrary to current literature, where a negative correlation is described (Peterson et al, 2008;Bellia et al, 2013;de Souza et al, 2016;Elizondo-Montemayor et al, 2017). Rodriguez et al (2018) in a meta-analysis showed that patients given vitamin D had lower levels of TNF-alpha compared to control groups (n = 0.380; p = 0.04).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Positive correlations have also been found between vitamin D and TNF-alpha levels (r = 0.347; p = 0.009), which is contrary to current literature, where a negative correlation is described (Peterson et al, 2008;Bellia et al, 2013;de Souza et al, 2016;Elizondo-Montemayor et al, 2017). Rodriguez et al (2018) in a meta-analysis showed that patients given vitamin D had lower levels of TNF-alpha compared to control groups (n = 0.380; p = 0.04).…”
Section: Discussioncontrasting
confidence: 59%
“…A negative correlation between vitamin D level and body mass index (BMI) has been described in literature (O'Dell et al, 2002;Rovner et O'Brien, 2008;Anonymous, 2014;Bani-issa et al, 2017;Elizondo-Montemayor et al, 2017;Hajjaj-Hassoun et al, 2017;Kumaratne et al, 2017). For example, Bani-issa et al (2017) found that in patients with BMI of 30 kg/m 2 or more, there was a risk of more than five times for vitamin D deficiency than for patients with BMI below 25 kg/m 2 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A follow-up of old individuals ( n = 23, 55–86 years) for 12 months showed that vitamin D levels were significantly lower in the winter with an increase in the number of individuals presenting deficiency. In the same season, there was a significant increase of circulating IL-6, IL-8, IL-β-1, MCP-1, and TNF-α ( 80 ). The low-grade chronic inflammation has been associated with aging-related diseases, and suboptimal levels of vitamin D have been related to chronic diseases/overall mortality ( 81 84 ), suggesting that adequate levels of vitamin D could benefit the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Bone disease is also dependent upon several host factors. Gender, age, and body mass index (BMI) are associated with lower vitamin D levels and increase systemic TNF-α (63). Lower estrogen levels increase bone resorption and osteoporosis (64).…”
Section: Host Factorsmentioning
confidence: 99%